Variability in body measurements of Bactrian Camels in South Kazakhstan. Оңтүстік Қазақстандағы бактриан түйелерінің дене өлшемдерінің өзгеруi. Изменение промеров тела у двугорбых верблюдов Южного Казахстана. - Nurseitova, M.; Muratova, B. R.; Orynbassarova, A.; Bazarbayeva 3, T.; Konuspayeva, G.; Faye, Bernard (Eurasian Journal of Ecology, 2016)
The aim of the present paper was to give a short description of the body measurements of double-humped camels in South-Kazakhstan, and to evaluate the changes of these body measurements along the lactation. Inthe frame of one experiment, four Bactrian camels were monitored and their body measurements regularly reported. The hump weight was estimated and the links with the body weight were assessed. Жұмыстың негiзгi мақсаты Оңтүстiк Қазақстандағы екi өркештi түйенiң дене пiшiмiнiң өзгерiсi және лактация кезiнде дене өлшемiнiң өзгерiсiн бағалау туралы қысқаша анықтама беру. Эксперимент барысында, екі өркештi төрт түйенiң дене пiшiмi алынды. Өркешi және дене салмағы бағаланды.В данный статье рассмотрены измерения промеров тела двугорбых верблюдов в Южном Казахстане и дана оценка изменениям промеров тела в период лактации. Во время эксперимента у четырех двухгорбых верблюдов были взяты промеры тела. Оценивались вес горба и масса тела.